Delirious Hopes: Napoleonic Milan and the Rise of Modern Italian Operatic Criticism. (31st July 2015) - Senici, Emanuele
Abstract This article explores the relationship between politics, society and culture in Napoleonic Milan (1796–1814) on the one hand, and opera reviews published in the city's periodical press at the time on the other. This relationship is worth discussing for two reasons: first, Milan under French rule constituted the earliest, embryonic instance of the modern city in Italy; second, it was there that for the first time in Italy operatic criticism shifted from an undivided focus on the performance, mostly treated as a social occasion, to a prominent concern for the work being performed, which became the object of lengthy critical scrutiny. The article focuses specifically on the function of the periodical press as a crucial link between the discourse of opera and that of the city, exploring the complex ways in which Milanese society, culture and ideology, especially as represented in the city's newspapers, are connected to the epoch-making shift from performance to work in the opera reviews published there.